2018
DOI: 10.1186/s12944-018-0767-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between three common single nucleotide polymorphisms (rs266729, rs2241766, and rs1501299) of ADIPOQ and cardiovascular disease: a meta-analysis

Abstract: BackgroundInconsistencies have existed in research findings on the association between cardiovascular disease (CVD) and single nucleotide polymorphisms (SNPs) of ADIPOQ, triggering this up-to-date meta-analysis.MethodsWe searched for relevant studies in PubMed, EMBASE, Cochrane Library, CNKI, CBM, VIP, and WanFang databases up to 1st July 2017. We included 19,106 cases and 31,629 controls from 65 published articles in this meta-analysis. STATA 12.0 software was used for all statistical analyses.ResultsOur resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…The results of meta-analysis revealed a number of contradictions with regard to associations of the rs266729 SNP and cardiovascular morbidity [7,8]. Apparently, associations between various SNPs and adiponectin concentrations are manifested differentially depending on the ethnic background of recruited cohorts of the subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of meta-analysis revealed a number of contradictions with regard to associations of the rs266729 SNP and cardiovascular morbidity [7,8]. Apparently, associations between various SNPs and adiponectin concentrations are manifested differentially depending on the ethnic background of recruited cohorts of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, associations described in various studies in different populations are variable apparently due to differences in ethnicity of the participating subjects, study design, cohort size, environmental effects, etc. [7,8,9]. Only a few studies have investigated the SNPs of the ADIPOQ gene in Russia [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Significant associations of ADIPOQ rs2241766 T>G genotype with CVD were observed in Caucasians but not in Asians, hence proposing a potential influence of ethnicity in genetic background. 28 The latest meta-analysis which was carried out by Kanu et al 29 reported that ADIPOQ rs2241766 variant was related with the elevated risk of CAD in various genetic models (allelic, dominant and recessive).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adiponectin has important role in regulating bone metabolism, inhibiting the osteoprotegerin expression in the osteoblasts and, also, by increasing the differentiation of osteoclasts [41]. Therefore, the ADIPOQ is an important candidate gene, since it has already been associated with metabolic disorders, including arthritis, osteonecrosis and obesity in humans [4244]. Moreover, this gene acts in several BP possibly involved with the causes of FHS in broilers, as discussed in our study, including lipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been considered a potent endogenous inhibitor of adipose triglyceride lipase ( ATGL) revealing a unique mechanism governing lipolysis and fatty acid availability [49]. Zhang and coworkers [44] evidenced that the G0S2 acts as a master regulator of tissue-specific balance of triglycerides storage, mobilization, partitioning of metabolic fuels between adipose and liver, and of the whole-body adaptive energy response.…”
Section: Discussionmentioning
confidence: 99%